ANDREA FALCON (ed.), Brill's Companion to the Reception of Aristotle in Antiquity. Series: Brill's companions to classical reception. Series Editor Kyriakos N. Demetriou. Vol. 7. Leiden; Boston: Brill, 2016. ISSN 2213-1426, 288 pp. - HERRÁIZ OLIVA, Pilar (Revista Española de Filosofía Medieval, 2017)
Review of ANDREA FALCON (ed.), Brill's Companion to the Reception of Aristotle in Antiquity. Series: Brill's companions to classical reception. Series Editor Kyriakos N. Demetriou. Vol. 7. Leiden; Boston: Brill, 2016. ISSN 2213-1426, 288 pp.